An experimental study of inner ear injury in an animal model of eosinophilic otitis media. (March 2014) - Matsubara, Atsushi; Nishizawa, Hisanori; Kurose, Akira; Nakagawa, Takashi; Takahata, Junko; Sasaki, Akira
Abstract Conclusion: As the periods of intratympanic injection of ovalbumin (OVA) to the middle ear became longer, marked eosinophil infiltration in the perilymphatic space was observed. Moreover severe morphological damage of the organ of Corti was observed in the 28-day antigen-stimulation side. These results indicate that eosinophilic inflammation occurred in the inner ear and caused profound hearing loss. Objective: The purpose of the present study was to elucidate the inner ear damage in a new animal model of eosinophilic otitis media (EOM) which we recently constructed. Methods: We constructed the animal model of EOM by intraperitoneal and intratympanic injection of OVA. Infiltrating cells and the inner ear damage were examined by histological study. Results: In the inner ear, a few eosinophils were seen in the scala tympani of the organ of Corti and the dilation of capillaries of the stria vascularis was observed in the 7-day stimulation side. In the 14-day antigen stimulation side, some eosinophils and macrophages were seen in not only the scala tympani but also the scala vestibule. In the 28-day antigen-stimulation side, severe morphological damage of the organ of Corti and many eosinophils, red blood cells, and plasma cells infiltrating the perilymph were observed.